Advanced MR Imaging of Peripheral Nerve Sheath Tumors Including Diffusion Imaging - Soldatos, Theodoros; Fisher, Stephen; Karri, Sirisha; Ramzi, Abdulrahman; Sharma, Rohit; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2015)
Peripheral nerve sheath tumors (PNSTs) are neoplasms derived from neoplastic Schwann cells or their precursors. Whereas benign PNSTs are relatively common and considered curable lesions, their malignant counterparts are rare but highly aggressive and require early diagnosis and treatment. MR imaging has been the modality of choice for noninvasive evaluation of PNSTs. This article discusses the features of PNSTs in conventional and advanced MR imaging, and it emphasizes the features that help differentiate benign and malignant variants.
Keywords: peripheral nerve sheath tumor; magnetic resonance imaging; magnetic resonance neurography; diffusion-weighted imaging; diffusion tensor imaging